1997
DOI: 10.1152/ajpheart.1997.272.2.h851
|View full text |Cite
|
Sign up to set email alerts
|

Arterial expansive remodeling induced by high flow rates

Abstract: The effects of chronic increase in aortic blood flow on arterial wall remodeling were investigated in vivo with the use of an aortocaval fistula (ACF) model in rats. Phasic hemodynamics and aortic wall structure upstream and downstream in 30 male Wistar rats with ACF and 30 sham-operated rats were compared immediately and 2 mo after the ACF was opened in anesthetized rats. Opening the ACF upstream acutely decreased aortic pressure (-30%, P < 0.001) and increased aortic blood velocity (x12, P < 0.001), blood fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 0 publications
5
122
0
4
Order By: Relevance
“…In animal models, creation of an aortocaval shunt is associated with a marked increase in aortic flow and shear stress followed by a progressive increase in aortic diameter, which tends to restore aortic shear stress to control levels. 14 Similarly, in our study participants, higher body weight, which is associated with increased resting cardiac output, was associated with increased aortic diameter. Thus, experimental models and data from humans suggest that aortic diameter is actively modulated in response to physiological stimuli.…”
Section: Discussionsupporting
confidence: 71%
“…In animal models, creation of an aortocaval shunt is associated with a marked increase in aortic flow and shear stress followed by a progressive increase in aortic diameter, which tends to restore aortic shear stress to control levels. 14 Similarly, in our study participants, higher body weight, which is associated with increased resting cardiac output, was associated with increased aortic diameter. Thus, experimental models and data from humans suggest that aortic diameter is actively modulated in response to physiological stimuli.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, several groups have reported that increased arterial flow elicits an increase of endothelium-derived vascular NO and cGMP levels. 6,50,51 Thus, NO-stimulated cell migration could serve as a wound-repair mechanism or it could also be involved in vascular remodeling that has been shown to occur in the presence of altered arterial flow. 6 A similar role can also be attributed to CNP on the basis of its existence in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…First, the low-resistance circuit resulting from creation of the AV anastomosis triggers an immediate increase in blood flow and wall shear stress (WSS) through the inflow artery (5)(6)(7). Second, these rapid increases in arterial blood flow and WSS stimulate an endothelium-dependent vasodilatory response in the artery and vein, mediated largely by nitric oxide (NO) and activation of matrix metalloproteinases (MMPs), that dilates both the inflow artery and outflow vein, restores WSS toward baseline, and inhibits neointimal hyperplasia development (7)(8)(9)(10)(11). Appropriate upregulation of MMPs results in matrix degradation and restructuring of the vascular scaffold, leading to luminal expansion (9,11,12).…”
Section: Vascular Remodeling and Neointimal Hyperplasia Developmentmentioning
confidence: 99%